TERORISME INTERNASIONAL DAN PENGARUH AL-QAEDA PASCA MENINGGALNYA OSAMA BIN LADEN - Agung Yudhistira Nugroho (Universitas 17 Agustus 1945 Jakarta, 2016)
al-Qaeda is one of the movement of global terrorism network that has a neat organizational structure and has established a strong chain of command and have an extensive network, greatly influenced by movements in sentiment toward the United States. WTC tragedy and other actions always lead to the infrastructure of Western countries, especially the U.S.. Osama Bin Laden as the leader of the al-Qaeda network has strong power in giving its influence in leading al-Qaeda. It can not be denied that Bin Laden was in first place most wanted people in the world. Under Bin Laden, al-Qaeda terrorist movement became a professional and highly coordinated, it can be seen from their actions is very neat. Osama bin Laden's death in 2011 and then, for some people is the end of the story of al-Qaeda. But the name of al-Qaida continues to appear in the news all over the world. In the name of the late al-Qaeda has been attributed to several events in the form of bomb attacks in Iraq, killing and conflict in Mali, clashes in Yemen, and sporadic raids and several incidents of kidnapping in Afghanistan. Looking at some of these cases the question